A new species of Acianthera (Orchidaceae, Pleurothallidinae) from the Cordillera Central of Colombia - Rincón-González, Milton; Sierra-Ariza, Mario Alexei; Karremans, Adam P. (Phytotaxa, 2020)
Acianthera Scheidweiler (1842: 292), a genus historically placed under the synonymy of Pleurothallis Brown (1813: 211), was reinstated by Pridgeon & Chase (2001) and redefined on the basis of molecular studies by Pridgeon et al. (2001). Additional DNA-based phylogenetic reconstructions, using broader sets of Acianthera species, resulted in further refinements in the circumscription of genus (Chiron et al. 2012, Karremans & Rincón-González 2015, Karremans et al. 2016).